Immunomodulatory role of estrogen in ischemic stroke: neuroinflammation and effect of sex - Zhong, Xiaojun; Sun, Yulin; Lu, Yajun; Xu, Lei (Frontiers in Immunology, 2023)
Although estrogen is predominantly related to the maintenance of reproductive functioning in females, it mediates various physiological effects in nearly all tissues, especially the central nervous system. Clinical trials have revealed that estrogen, especially 17β-estradiol, can attenuate cerebral damage caused by an ischemic stroke. One mechanism underlying this effect of 17β-estradiol is by modulating the responses of immune cells, indicating its utility as a novel therapeutic strategy for ischemic stroke. The present review summarizes the effect of sex on ischemic stroke progression, the role of estrogen as an immunomodulator in immune reactions, and the potential clinical value of estrogen replacement therapy. The data presented here will help better understand the immunomodulatory function of estrogen and may provide a basis for its novel therapeutic use in ischemic stroke.